Uptake and catabolism of D-xylose in Salmonella typhimurium LT2. - Shamanna, D K (1979)
Salmonella typhimurium LT2 grows on D-xylose as sole carbon source with a generation time of 105 to 110 min. The following activities are induced at the indicated time after the addition of the inducer, D-xylose: D-xylulokinase (5 min), D-xylose isomerase (7 to 8 min), and D-xylose transport (10 min). All other pentoses and pentitols tested failed to induce isomerase or kinase. Synthesis of D-xylose isomerase was subject to catabolite repression, which was reversed by the addition of cyclic adenosine monophosphate. Most of the radioactive counts from D-[14C]xylose were initially accumulated in the cell in the form of D-xylose or D-xylulose. D-Xylose uptake in a mutant which was deficient in D-xylose isomerase was equal to that of the wild type. The apparent Km for D-xylose uptake was 0.41 mM. Some L-arabinose was accumulated in D-xylose-induced cells, and some D-xylose was accumulated in L-arabinose-induced cells. D-Xylitol and L-arabinose competed against C-xylose uptake, but D-arabinose, D-lyxose, and L-lyxose did not. Osmotic shock reduced the uptake of D-xylose by about 50%; by equilibrium dialysis, a D-xylose-binding protein was detected in the supernatant fluid after spheroplasts were formed from D-xylose-induced cells.